ANALYSIS OF PROPERTIES OF CONCRETE USING HENS FEATHER DIPPED IN SALT WATER AS FIBRE REIGFORCEMENTADMIXTURE - Gadgihalli, Vishal; Meena; Anusha; Hilal, Aiman; Dinakar, Raghavendra Prasad (International Journal of Research -GRANTHAALAYAH, 2017)
A material other than water, aggregates, or cement that is used as an ingredient concrete or mortor to control setting and early hardening, workability, or to provide additional cementing properties. In this paper analysis of properties of concrete using hen’s feathers dipping in saltwater as admixture is studied and verified the strength of concrete to the normal Portland cement. As hens feather are most complex integumentary appendages formed in tie follicles in the epidermis, or outer skin layer that produce keratin proteins.